Volume 5B: 40th Mechanisms and Robotics Conference 2016
DOI: 10.1115/detc2016-59060
|View full text |Cite
|
Sign up to set email alerts
|

Highly Compressible Origami Bellows for Harsh Environments

Abstract: The use of origami-based bellows is of interest in fields where traditional metal bellows are incapable of meeting compression, mass, or flexibility constraints. Metal bellows are often used in space applications but frequently complicate spacecraft design. Origami-based bellows capable of meeting design constraints while adequately shielding sensitive spacecraft parts may be advantageous to space mechanism design. The design and testing of a highly compressible origami bellows for harsh environments is descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 15 publications
(24 reference statements)
0
21
0
Order By: Relevance
“…For more rigorous testing, the Kresling-based origami bellows was selected, as its fatigue behavior at room temperature is better characterized than the Yoshimura pattern. As such, the Kresling fold template provided by Butler et al was printed out and affixed to a desk [14,15]. Samples of BoPET were cut to fit the template, folds pre-scored with a flat-head screwdriver, and then hand-folded into shape.…”
Section: Bellows Fabrication and Linear Actuation Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…For more rigorous testing, the Kresling-based origami bellows was selected, as its fatigue behavior at room temperature is better characterized than the Yoshimura pattern. As such, the Kresling fold template provided by Butler et al was printed out and affixed to a desk [14,15]. Samples of BoPET were cut to fit the template, folds pre-scored with a flat-head screwdriver, and then hand-folded into shape.…”
Section: Bellows Fabrication and Linear Actuation Testsmentioning
confidence: 99%
“…Their origami bellows, constructed from materials including Mylar™ and Kapton™, all survived ≥ 10,000 actuation cycles before pinholes in the polymer film developed. These bellows were more compressible (the collapsed length of a given bellows is < 10 % of the deployed length) and less massive than traditional metal bellows [15]. In determining if the fatigue resilience of origami bellows extended from room temperature to 77 K, Reid actuated a Hexagonal bellows, fabricated from 101 µm thick Kapton™, for 500 cycles in liquid nitrogen without failure.…”
Section: Introductionmentioning
confidence: 99%
“…Previous compliant mechanism research has demonstrated origami-based bellows capable of compression ratios exceeding 1:30, compared to 1:8 for metal bellows, making them a strong candidate in bellows design for space mechanisms. 16 Use of an origami-based bellows would achieve the desired compressibility while significantly reducing mass ( Figure 4) and the parasitic reaction forces in the bellows.…”
Section: Drill Bitmentioning
confidence: 99%
“…7 The benefits of origami-based space design have been demonstrated as viable and effective in NASA's star shade, 8 deployable solar panels, 9 parabolic antennas, 10 pneumatic solar tracking systems, 11 inflatable structures, 12,13 the James Webb telescope, Lang's Eyeglass, 14 sunshields for space telescopes, 15 and highly compressible bellows. 16 The benefits of origami created an opportunity for application on NASA's Asteroid Redirect Mission (ARM). The ARM would collect a multi-ton boulder and use the boulder to perform an Enhanced Gravity Tractor asteroid deflection demonstration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation